2015
DOI: 10.1016/j.colsurfa.2015.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Gold(III) extraction and recovery and gold(III)/copper(II) separation using micelles

Abstract: Gold extraction from aqueous solutions has been performed by micellar enhanced ultrafiltration (MEUF), using SDS and DTAC micelles. DTAC entraps 92-100% of the metal, which is present in form of AuCl4-, owing to electrostatic interaction. Using SDS the extraction of gold is unsuccessful. However, addition of PADA, as a metal extractor agent, according to the ligand modified micellar enhanced ultrafiltration (LM-MEUF) procedure, makes the extraction yield to approach 100% also with SDS. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The commercially available ligand PADA ( Figure 1) is totally adsorbed on a variety of surfactants, including SDS [4] and has proven to be an excellent metal extractor, being able to transfer metal ions from water to micellar phases with yields approaching 100% [5][6][7] Moreover, we have found that PADA is able to complex Au(III) with great affinity even if the coordination shell of the metal is occupied, as in AuCl4 - [8,9]. In this case, a molecule of PADA replaces two chloride ions forming a strong chelate.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The commercially available ligand PADA ( Figure 1) is totally adsorbed on a variety of surfactants, including SDS [4] and has proven to be an excellent metal extractor, being able to transfer metal ions from water to micellar phases with yields approaching 100% [5][6][7] Moreover, we have found that PADA is able to complex Au(III) with great affinity even if the coordination shell of the metal is occupied, as in AuCl4 - [8,9]. In this case, a molecule of PADA replaces two chloride ions forming a strong chelate.…”
Section: Introductionmentioning
confidence: 87%
“…The stock solutions of these reactants were prepared by dissolving appropriate amounts of the relevant solid material in water. The gold content was determined by direct UV absorption spectrometry exploiting the absorption band of AuCl4ion centred at 233 nm whose maximum absorption is proportional to the gold concentration [8,9]. Water, purified by pumping deionized water through a Milli-Q apparatus, was used to prepare the solutions and also as the reaction medium.…”
Section: Methodsmentioning
confidence: 99%
“…Then, 10 mL of every solution was passed across the membrane (cutoff 1000 Da) under 60 bar of nitrogen pressure. When 8 mL of the initial solution has been filtered, the concentration of TPPS in the filtrate was measured by UV–vis spectroscopy (PerkinElmer Lambda 650 spectrophotometer—San Francisco, CA, USA), and then the percentage of retention ( R %) was calculated by the following equation [ 86 ]: where Ap and Ai are the absorbance of TPPS in the permeate and in the initial solution, respectively, at a given wavelength. R % were calculated at different wavelengths (corresponding to signal maxima) and averaged.…”
Section: Methodsmentioning
confidence: 99%
“…Then, 10 mL of every solution was passed across the membrane (cutoff 1000 Da) under 60 bar of nitrogen pressure. When 8 mL of the initial solution has been filtered, the concentration of TPPS in the filtrate was measured by UV-vis spectroscopy (PerkinElmer Lambda 650 spectrophotometer-San Francisco, CA, USA), and then the percentage of retention (R%) was calculated by the following equation [86]:…”
Section: Ultrafiltrationmentioning
confidence: 99%
“…Cu(II) removal could not be achieved by cationic DTAC micelles. But they could provide gold-copper separation by MEUF to a large extent utilizing charge effect of SDS micelles: oppositely charged Cu(II) ions bound to micelles retained on the membrane, while AuCl 4 − ions of the same charge with micelles passed through the permeate [52].…”
Section: Ligand-modified Micellar-enhanced Ultrafiltrationmentioning
confidence: 99%